2024
DOI: 10.1111/pim.13023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the immune response and protection against the experimental Toxoplasma gondii infection elicited by immunization with the recombinant proteins BAG1, ROP8, and BAG1ROP8

Yien Xing,
Jun Yang,
Pengjing Yao
et al.

Abstract: Toxoplasmosis is one of the most dangerous zoonotic diseases, causing serious economic losses worldwide due to abortion and reproductive problems. Vaccination is the best way to prevent disease; thus, it is imperative to develop a candidate vaccine for toxoplasmosis. BAG1 and ROP8 have the potential to become vaccine candidates. In this study, rTgBAG1, rTgROP8, and rTgBAG1‐rTgROP8 were used to evaluate the immune effect of vaccines in each group by detecting the humoral and cellular immune response levels of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In the establishment of immune memory, the application of the vaccine also showed remarkable results [222][223][224][225]. It was found that after inoculation with mannose-modified lipid calcium phosphate nanoparticles, the body can form a long-term memory of tumor antigens [226].…”
Section: Enhancement Of Tumor Immune Response and Establishment Of Im...mentioning
confidence: 99%
“…In the establishment of immune memory, the application of the vaccine also showed remarkable results [222][223][224][225]. It was found that after inoculation with mannose-modified lipid calcium phosphate nanoparticles, the body can form a long-term memory of tumor antigens [226].…”
Section: Enhancement Of Tumor Immune Response and Establishment Of Im...mentioning
confidence: 99%